A large-size HfO₂ based RRAM structure suitable for integration of one RRAM with one InGaZnO thin film transistor for large-area applications - Li, Yuanbo (2022)
This work aims at finding a HfO2-based resistive random-access memory (RRAM) structure suitable for the integration of one RRAM with one InGaZnO thin film transistor (TFT) for large-area applications such as flexible electronic circuits. One of the major concerns is that the compliance current (CC) required for the formation of stable and strong conductive filaments in the forming and set processes as well as the maximum current required in the reset process in a large-size RRAM should be lower than that of the maximum current a TFT can deliver. In this work, an ultrathin Al2O3 layer of 2 nm was inserted between the HfO2 switching layer and the reactive Ti layer of the top electrode in the RRAM with the structure of Pt (bottom electrode)/HfO2/Al2O3/Ti/TiN (top electrode). With the ultrathin Al2O3 layer, the forming voltage was greatly reduced, and the CC for stable forming and set operations and maximum reset current can reach a low current level that an InGaZnO TFT is able to provide, while the device-to-device variation of the forming operation and cycle-to-cycle resistance variations of the set and reset operations are improved significantly.